The Application of graphic visualization filters for Historical-Archaeological Studies. A case of study: “Mesas del Esparragal”, Alcalá de Los Gazules, Cádiz (Spain) - Catalán González, Francisco Javier (Peer Community Journal, 2025)

(untitled)
The aim of this article consists in a presentation and a comparison of filters for the detection of archaeological structures developed through open-source Geographical Information Systems tools applied to the surface of the archaeological site known as Mesas del Esparragal, located in the municipality of Alcalá de los Gazules (Cádiz, Spain). The site, identified by some researchers as Lascuta because of its relationship with the famous Lascuta Bronze, has exceptional characteristics in terms of its strategic position for controlling the territory. For this reason, the Romans at the hands of the consul Lucius Emilius Paulus, were able to establish their camp in this important place with the aim of putting down the uprising perpetuated by the city of Hasta Regia. For this purpose, the data obtained through the LiDAR sensor collected by the National Plan for Aerial Orthophotography (PNOA) will be used. These data will be classified by means of the LASTools complement and later a series of filters will be made through the Relief Visualization Toolbox (RVT) software and the SAGA software, with the purpose of comparing them and determining which filter or filters are the most appropriate when locating possible archaeological structures under the surface. The filters to be compared are: The Three-directional Hillshade, the Simple Local Relief Model (SLRM) and the Red Relief Image Map (RRIM).